Calculation and Analysis of Meshing Contact of Involute Spur Gear - Yuda Wang; Lü Hongzhan; Zhiyong Hou; Shuyan Wang; Weiguang Ma; Feng Li (Jixie chuandong)
The analysis of meshing process of involute spur gear is an important basis to judge the transmission quality，and especially contact stress，transmission error and meshing stiffness are key indexes. According to the TCA model of spur gear，curvature radii in different meshing points are extracted. The meshing process of tooth surface is simplified as elastic extrusion between pairs of cylinders with different radii. Considering the load distribution between the teeth，the Hertz principle is used to carry out load-bearing contact analysis on the tooth surface. It shows that the results of this method are quite same as the results obtained by FEM and experiment. The error of the maximum of the contact stress is 0.74%.The results of transmission error and meshing stiffness are essentially same. The dynamic process of tooth surface contact and meshing stiffness can be reflected by this analysis method.